BANK SYARIAH DAN BANK KONFESIONAL DENGAN NILAI DAN KANDUNGAN TERHADAP PERBEDAAN PENERAPAN DAN PENEGELOLAAN KINERJA KEUANGAN SECARA SYARIAH DAN KONFESIONAL - Jairin Jairin (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2021)
The name of someone, something, institution had a certain meaning. A meaning depended so much on someone’s perception to an object. Perception of society to Sharia Bank had an impact to society behavior towa rd Sharia Bank. There was a gap here between bank and society which had to be acted as a bridge through policy and socialization program. Socialization policy which was planned, adaptive, and interesting could minimize the misperception risk. Socially, sosialization program was the enculturization of sharia bank values process, and it was understood as the form of civil education.